The Greek theatre and festivals: documentary studies ; [colloquium, held in Oxford on 14 - 15 July 2003] - Wilson, Peter (Oxford studies in ancient documents, 2007)
Deconstructing festivals / William Slater -- Theatre rituals / Angelos Chaniotis -- The organisation of music contests in the Hellenistic period and artists' participation : an attempt at classification / Sophia Aneziri -- The men who built the theatres : theatropolai, theatronai, and arkhitektones / Eric Csapo ; with an archaeological appendix by Hans Rupprecht Goette -- Choregic monuments and the Athenian democracy / Hans Rupprecht Goette -- Performance in the Pythion : the Athenian Thargelia / Peter Wilson -- Dithyramb, tragedy, and Cyrene / Paola Ceccarelli and Silvia Milanezi -- A horse from Teos : epigraphical notes on the Ionian-Hellespontine Association of Dionysiac Artists / John Ma -- Kraton, son of Zotichos : artists' associations and monarchic power in the Hellenistic period / Brigitte Le Guen -- Theoria and theatre at Samothrace : the Dardanos by Dymas of Iasos / Ian Rutherford -- The Dionysia at Iasos : its artists, patrons, and audience / Charles Crowther -- An opisthographic lead tablet from Sicily with a financial document and a curse concerning choregoi / David Jordan -- Sicilian choruses / Peter Wilson